Quantifying Greenhouse Gas Emissions of Water Buffalo by Age Category in Central Aurora, Philippines - Delos Santos, Daniel T.; Torres, Michael M.; Peria, Jo Neil T. (Future Science / FSH-PH Publications, 2025)
The rise in global greenhouse gases, particularly methane from agricultural water buffalo, poses a significant climate threat. This study aimed to quantify methane and nitrous oxide emissions from these buffalo in Central Aurora, Philippines, where such data is currently unquantified. The objective was to provide local and national policymakers with specific emission data to develop targeted mitigation policies, reducing the environmental impact of buffalo farming while sustaining its benefits. The data were collected from farms and government offices, supplemented by expert discussions. IPCC Tier 1 emission factors with uncertainty value of 60%, specific to Southeast Asia and buffalo age categories, were used with population data to calculate annual methane and nitrous oxide emissions, expressed as CO₂ equivalents also referring to all different warming gases in the atmosphere. Yearling buffalo were the highest individual methane emitters, emphasizing the need for targeted management during this stage to reduce overall emissions. Adult buffaloes contributed most to nitrous oxide emissions, highlighting the importance of age-specific emission factors for accurate inventories. Overall, water buffalo farming significantly contributed to greenhouse gases, necessitating age-aware and manure management strategies for mitigation. The highest CO₂ emissions was mainly due to methane released during their growth. Adult buffalo, though individually less polluting, contributed substantially to overall emissions because of their numbers. For precise evaluations, it was crucial to consider age-specific emission factors. This highlighted the importance of targeting yearlings with mitigation strategies (like changes in diet) and implementing wider management practices for adult herds, especially in agricultural planning for areas like Aurora, Central Luzon. While future studies may employ Tier 2 methods or examine genetic and dietary modifications to further refine emission estimates.